Use of Technology to Promote Child Behavioral Health in the Context of Pediatric Care: A Scoping Review and Applications to Low- and Middle-Income Countries - Huang, Keng-Yen; Lee, Douglas; Nakigudde, Janet; Cheng, Sabrina; Gouley, Kathleen Kiely; Mann, Devin; Schoenthaler, Antoinette; Chokshi, Sara; Kisakye, Elizabeth Nsamba; Tusiime, Christine; Mendelsohn, Alan (Frontiers in Psychiatry, 2019)
Background: The burden of mental, neurological, and substance (MNS) disorders is greater in Low- and Middle-Income Countries (LMICs). The rapid growth of digital health (i.e., eHealth) approaches can provide new solutions for transforming pediatric mental health services, and have the potential to address multiple resources and system barriers. However, little work has been done in applying eHealth to promote young children’s mental health in LMICs. It is also not clear how eHealth has been and might be applied for translating existing evidence-based practices/strategies (EBPs) to broader child mental health interventions and service access. Methods: A scoping review was conducted to summarize current eHealth applications and evidence in child mental health. The review focuses on 1) providing an overview of existing eHealth applications, research methods, and effective evidence in child mental health promotion (focused on children of 0-12 years of age) in diverse service contexts; and 2) drawing lessons learned from the existing research about the eHealth design strategies and usability evidence to inform future eHealth design in LMICs. Results: 32 articles fitting our inclusion criteria were reviewed. The child mental health eHealth studies were grouped into three areas: i) eHealth interventions targeting families (for parents and child); ii) eHealth for improving school mental health services (e.g., to promote school staff’s knowledge and management skills); and iii) eHealth for improving behavioral health care in the pediatric care system (e.g., to promote use of integrated patient-portal and electronic decision support systems that improve child behavioral health care). Most eHealth studies have reported positive impacts. Although most pediatric eHealth studies were conducted in high-income countries, many eHealth design strategies can be adapted and modified to fit LMIC contexts. Most user-engagement strategies identified from high-income countries are also highly relevant for populations in LMICs. Conclusions: This review synthesizes patterns of eHealth use across a spectrum of individual/family and system level of eHealth interventions that can be applied to promote child mental health and strengthen mental health service systems. This review also summarizes critical lessons to guide future eHealth design in LMICs. However, more research in testing combinations of eHealth strategies in LMICs is needed.